The Rôle of Human Platelets and Plasma in the Metabolism of Adenosine Diphosphate and Monophosphate Added In Vitro - Kerby, G. P; Taylor, S. M (Thrombosis and Haemostasis, 1964)
When exogenous adenosine monophosphate (AMP) and diphosphate (ADP) were added to sonicated platelet-rich human blood plasma in AMP-ADP ratio approximating that normally present in platelets, a ratio close to 1.0 was consistently established within 20 to 60 minutes of incubation at 37° C. This resulted both from progressive disappearance of ADP and from initial augmentation followed by disappearance of AMP, the disappearance of ADP always being greater however than the disappearance of AMP so that the higher ratio was maintained.AMP appeared as ADP disappeared during the first 20 minutes of incubation. Platelet adenylate kinase, plasma 5-adenylic acid deaminase and nonspecific alkaline phosphatases appeared to be of particular importance in achieving the changing ratios of nucleotides.